Visual Working Memory of Chinese Characters and Expertise: The Expert’s Memory Advantage Is Based on Long-Term Knowledge of Visual Word Forms - Zimmer, Hubert D.; Fischer, Benjamin (Frontiers in Psychology, 2020)
People unfamiliar with Chinese characters show poorer visual working memory (VWM) performance for Chinese characters than do literates in Chinese. In a series of experiments, we investigated the reasons for this expertise advantage. Experiments 1 and 2 showed that the advantage of Chinese literates does not transfer to novel material. Experts had similar resolution as novices for material outside of their field of expertise, and the memory of novices and experts did not differ when detecting a big change; e.g., when a character’s color was changed. Memorizing appears to function as a rather abstract representation of word forms because memory for characters’ fonts was poor independently of expertise (Experiment 3), though still visual. Distractors that were highly similar conceptually did not increase memory errors, but visually similar distractors impaired memory (Experiment 4). We hypothesized that literates in Chinese represent characters in VWM as tokens of visual word forms made available by long-term memory. In Experiment 5, we provided novices with visual word form knowledge. Participants subsequently performed a change detection task with trained and novel characters in a functional magnetic resonance experiment. We analyzed set size and training dependent effects in the intraparietal sulcus (IPS) and the visual word form area. VWM for trained characters was better than for novel characters. Neural activity increased with set size and at a slower rate for trained than for novel characters. All conditions approached the same maximum, but novel characters reached the maximum at a smaller set size than trained characters. The time course of the bold response depended on set size and knowledge status. Starting from the same initial maximum, neural activity at small set sizes returned to baseline more quickly for trained characters than for novel characters. Additionally, high performers showed generally more neural activity in the IPS than low performers. We conclude that experts’ better performance in WM is caused by the availability of visual long-term representations (word form types) that allow a sparse representation of the perceived stimuli and make even small changes big because they cause a type change that is easily detected.